Differential analysis of student and teacher instructional expectations - Johnson, M. L., author; Davies, Timothy Gray, advisor; Porter, Charles F., committee member; Jansen, Duane, committee member; Morgan, George A., committee member (Colorado State University. Libraries, 2003)
The purpose of this study was to determine if students and teachers differed in their expectations of classroom instruction. Professional experience and empirical evidence indicate that there may be significant classroom instruction expectation differences held by higher education students and faculty. Differences in the rate and amount of work expectations are only two of the more obvious variables. The central problem of unrecognized expectation differences between the two parties is that frustration is increased and learning is impeded. Numerous problems can arise from classroom miscommunication. The several players each have their own expectations of higher education classroom instruction. The exact expectation differences between students and faculty have not been elucidated. The present study was intended to address the possibility of such group differences and, subsequently, to improve post-secondary instruction. In order to get a structured and comparable response to student and faculty expectations, a questionnaire was developed and tested over a period of several years. The instrument was designed to measure response to the following factors: (a) Knowledge transmission; (b) Classroom entertainment; (c) Intellectual challenge; (d) Psychological support; (e) Achievement responsibility, and (f) Formatting the class to the textbook. Eighty-six students and 85 teachers from northern Colorado Front Range community colleges completed the 12-item questionnaire. Forty-three male faculty, 41 female faculty, 43 female students and 43 male students served as subjects. The data were analyzed by correlation for reliability estimates, by ANOVA techniques to assess mean group score differences and by mean score and standard deviation estimate for effect size. The significant group expectation results showed that students expect information to be more formally structured for "knowledge transmission," more "entertainment and media," less "intellectual challenge" and for classes to be formatted "to the textbook." There were no statistical student-faculty differences in regard to "psychological support" or "responsibility for student achievement". Further, there were no significant sex differences between the data pooled by student and faculty categories and there were no significant interactions between faculty-student status and male-female sex categories. The 150 unit visual analog scale for each item, from agree to disagree, allowed a degree of estimate gradation. Though there were significant differences, both entertainment and challenge factors had relatively high ratings for both students and faculty. There were no differences between students and faculty regarding physiological support, but those ratings were relatively high. Effect size, using the d family index, was computed for each factor. The d values for the two factors that were not statistically significant were low and the values for moderate to high for other factors. The highest effect size value was for the knowledge transmission factor. Awareness and discussion of the differences in faculty and student expectations could be the basis of interventions for raising student achievement, facilitating sophistication of cognitive development and reducing institutional dropout rates. A simple instrument, such as the one used in this study, could serve as the basis of faculty-student expectations discussion early in the course.
Keywords: community colleges; curricula; teaching; curriculum development; community college education